The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/3-540-45636-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Regularities in the Formation and Evolution of Information Cities

Abstract: Abstract. In the real world, cities exist because of external economies associated with the geographic concentration of firms within a city. Of course, such a geographic proximity with input providers and consumers, would at first reduce transportation costs. But why cities, information cities, i.e. large agglomerations of people and economic activity emerge in the virtual world? In the Internet, transportation costs are zero. Web sites can easily be reached from anybody and everywhere with no particular cost.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The simulation output is a sequence of statistic vectors containing numbers of visits per each site taken at every N th step. The simulation has shown that the distribution of users per sites follows a universal power law [1]. Note that the model is stochastic.…”
Section: Agent-based Modeling and Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation output is a sequence of statistic vectors containing numbers of visits per each site taken at every N th step. The simulation has shown that the distribution of users per sites follows a universal power law [1]. Note that the model is stochastic.…”
Section: Agent-based Modeling and Simulationmentioning
confidence: 99%
“…The "word of mouth" (WoM) simulation model is a stochastic socio-economical model that addresses the real-world phenomena of the behavior of the Internet population [1]. The model of time is discrete.…”
Section: Agent-based Modeling and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…If the vertexes 1, and 4 are going to be rewired concurrently, the edges (1, 2) and (4, 5) will be deleted. The possible edges to insert are: vertex -1 = (1, 2), (1, 3), (1,4), (1,5); and vertex-4 = (4, 5), (4,6), (1,4), (2,4). The edge (1, 4) can be added by both processes.…”
Section: The Motivation Approaches and Problemsmentioning
confidence: 99%
“…The sequential agent-based simulation environment can be found in [2]. Also, one of the implemented behavior models can be reviewed in [5]. The parallel environment is under publication [3].…”
Section: Introductionmentioning
confidence: 99%